2021
DOI: 10.3390/cells10061512
|View full text |Cite
|
Sign up to set email alerts
|

ABHD4-Regulating RNA Panel: Novel Biomarkers in Acute Coronary Syndrome Diagnosis

Abstract: Background: Acute coronary syndrome (ACS) is a major cause of death all over the world. STEMI represents a type of myocardial infarction with acute ST elevation. We aimed to assess the predictive power of potential RNA panel expression in acute coronary syndrome. Method: We used in silico data analysis to retrieve RNAs related to glycerophospholipid metabolism dysregulation and specific to ACS that results in the selection of Alpha/Beta hydrolase fold domain4 (ABHD4) mRNA and its epigenetic regulators (Foxf1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that SBP can improve endothelial dysfunction. Since endothelial dysfunction is a key factor in cardiovascular system diseases development, restoring and maintaining endothelial cells normal function has been considered as an effective treatment for ACS [13] . When the coronary arteries stimulated, the endothelial barrier injured, the permeability increased and the accumulation of lipids and leukocytes into the intima accelerated, promoting vascular stenosis, then ischemic heart disease and stroke happened.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that SBP can improve endothelial dysfunction. Since endothelial dysfunction is a key factor in cardiovascular system diseases development, restoring and maintaining endothelial cells normal function has been considered as an effective treatment for ACS [13] . When the coronary arteries stimulated, the endothelial barrier injured, the permeability increased and the accumulation of lipids and leukocytes into the intima accelerated, promoting vascular stenosis, then ischemic heart disease and stroke happened.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, indepth analysis is needed to uncover the pathogenesis of ACS. Although a few thousands of lncRNAs have been functionally characterized in ACS, their potential mechanisms in ACS remain greatly indistinct [25][26][27]. In our study, we adopted microarray technology to obtain the expression data of lncRNAs and mRNAs in serum specimens from 4 patients with ACS and 4 healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Several novel biomarkers have been reported in recent years, including microRNAs [ 17 ] and long non-coding ribonucleic acids [ 18 ]. However, measuring these biomarkers is expensive, time-consuming, and complicated.…”
Section: Discussionmentioning
confidence: 99%